Screenplay of Asal-Muasal Tanah Jawa: A Prototype of The Babad Tanah Jawi Script Content Saving Through Adaptation - Irwan Sarbeni; Dheka Agustiningsih; Muhammad Tiffano Zetha El-Xavier (Institut Seni Indonesia Denpasar, 2023)
Babad Tanah Jawi is one of the masterpieces of Javanese literature which contains kingdoms story in Java land which have been written in several versions. Javanese scholars deeply hopes that the constructive and forward-minded values contained in the Babad could be disseminated and studied by all levels of society, especially Java, in an easily understandable way and through a media that is close to society's daily, so that Javanese may recognize their original identity and avoid historical conflicts that come from non-primary sources. Therefore, Javanese scholars are very sorry when studies on the Babad always end up in formal writing that can only be accessed by a limited circle (academics). Responding to these problems, this research was carried on the behalf of studying the script text character of the Babad Tanah Jawi and adapt its Asal-muasal Tanah Jawa chapter content (The Origins of the Land of Java) to a screenplay (film script) as an act of salvaging the valuable content of the Babad script to a feature film. This research is presented qualitatively with ‘Adaptation’ method to compose the screenplay. The adaptation is an essential stage in filmmaking since a well-prepared film is largely determined by the quality of its creation guidelines (screenplay). This study resulted in fiction film screenplay. The screenplay is composed based on the hypogram script character of Asal-muasal Tanah Jawa which tends to present the story concisely so that the essence of the adaptation is emphasized on the clarity of the plot. To make each piece of the story in the Babad more logic and connected to each other, it is added some dramatical elements and events that are studied and concluded from external relevant sources of Asal-muasal Tanah Jawa.